2010
DOI: 10.1007/s00125-010-2013-4
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c levels in schoolchildren with type 1 diabetes are seasonally variable and dependent on weather conditions

Abstract: Aims/hypothesisWe evaluated seasonal HbA1c changes in children with type 1 diabetes and its relation with measures of weather conditions.MethodsHbA1c changes over more than 3 years were evaluated in type 1 diabetic patients who were younger than 18 years and had diabetes duration of more than 12 months, and correlated with measures of weather conditions (ambient temperature, hours of sunshine and solar irradiance). After comparison of autocorrelation patterns, patterns of metabolic control and meteorological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 25 publications
4
36
1
1
Order By: Relevance
“…Despite the fact that the present study contained a large amount of HbA1c measurements, a lot more than in most paediatric studies (4, 23), we could not confirm the seasonal variations during follow up that were found in other studies (4,23). Children and adolescents with type 1 diabetes in Sweden are intensively treated with multiple insulin injections or insulin pump therapy and active self-control.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Despite the fact that the present study contained a large amount of HbA1c measurements, a lot more than in most paediatric studies (4, 23), we could not confirm the seasonal variations during follow up that were found in other studies (4,23). Children and adolescents with type 1 diabetes in Sweden are intensively treated with multiple insulin injections or insulin pump therapy and active self-control.…”
Section: Discussioncontrasting
confidence: 69%
“…Seasonal variations in glycated haemoglobin (HbA1c) at follow-up have been observed in adults and children with type 1 diabetes, with the lowest values during the summer and the highest levels during the winter (1)(2)(3)(4)(5). Some studies have found the greatest seasonal variations in older age groups (4), but no gender differences have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference values for healthy people estimated by the local laboratory were from 4.3 to 5.7 %. The within-run coefficient of variation (CV) determined by the manufacturer was 1.05 % for normal patients and 0.94 % for diabetic patients; the between-run CV was 1.61 and 1.16 % for normal and for diabetic patients, respectively, as reported previously [16]. In all patients, the estimation of albumin excretion rate (AER) was obtained from overnight urine sample.…”
Section: Methodsmentioning
confidence: 81%
“…However, in clinical research it is little used. Of 12 seasonality papers in Medline (4 -15) , only two (12,15) applied autocorrelation, while the rest just reported the presence of a signifi cant difference between the mean data of different seasons. Autocorrelation does not demonstrate signifi cant differences between seasons, but rather signifi cantly repetitive patterns, meaning patterns that are stronger repetitive than could happen by chance.…”
Section: Introductionmentioning
confidence: 97%